2011
DOI: 10.1007/s11626-011-9457-9
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective activity of Tribulus terrestris extract against acetaminophen-induced toxicity in a freshwater fish (Oreochromis mossambicus)

Abstract: The potential protective role of Tribulus terrestris in acetaminophen-induced hepatotoxicity in Oreochromis mossambicus was investigated. The effect of oral exposure of acetaminophen (500 mg/kg) in O. mossambicus at 24-h duration was evaluated. The plant extract (250 mg/kg) showed a remarkable hepatoprotective activity against acetaminophen-induced hepatotoxicity. It was judged from the tissue-damaging level and antioxidant levels in liver, gill, muscle and kidney tissues. Further acetaminophen impact induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(40 citation statements)
references
References 50 publications
1
38
0
1
Order By: Relevance
“…Ramos et al (2014) observed that the fish species Oncorhynchus mykiss exposed to this compound showed a significant increase in both forms of glutathione peroxidase for acute tests at concentrations 5 orders of magnitude above (0.05, 0.5 and 5 mg L À 1 ) those used in the present study. Kavitha et al (2011) described noteworthy increases of GPx activities in the fish Oreochromis mossambicus after acute exposure to paracetamol, A marked increase in GPx activity was also observed in specimens of Cyprinus carpio after exposure to paracetamol (Nava-Álvarez et al, 2014). Similarly, increases in GPx activity have been described by Parolini et al (2010) after acutely exposing zebra mussel (Dreissena polymorpha) to acetaminophen, but also in other antioxidant enzymes (catalase, superoxide dismutase, and GSTs).…”
Section: Acetaminophenmentioning
confidence: 70%
See 1 more Smart Citation
“…Ramos et al (2014) observed that the fish species Oncorhynchus mykiss exposed to this compound showed a significant increase in both forms of glutathione peroxidase for acute tests at concentrations 5 orders of magnitude above (0.05, 0.5 and 5 mg L À 1 ) those used in the present study. Kavitha et al (2011) described noteworthy increases of GPx activities in the fish Oreochromis mossambicus after acute exposure to paracetamol, A marked increase in GPx activity was also observed in specimens of Cyprinus carpio after exposure to paracetamol (Nava-Álvarez et al, 2014). Similarly, increases in GPx activity have been described by Parolini et al (2010) after acutely exposing zebra mussel (Dreissena polymorpha) to acetaminophen, but also in other antioxidant enzymes (catalase, superoxide dismutase, and GSTs).…”
Section: Acetaminophenmentioning
confidence: 70%
“…1B). GPx enzymes belong to the glutathione (GSH) family, whose role is the removal of free radical species (such as hydrogen peroxide and superoxide radicals), and are also involved in the protection of membrane proteic thiols (Kavitha et al, 2011). The decrease in GPx activity in our study may indicate that its antioxidant capacity was surpassed by the amount of hydroperoxide products of lipid peroxidation, a hypothesis already raised by Monteiro et al (2006), or as a consequence of direct inactivation of the enzyme caused by reactive metabolites of paracetamol.…”
Section: Acetaminophenmentioning
confidence: 99%
“…Several pharmacological studies have revealed its cardioprotective [6], hepatoprotective [7]; antitumor [8], and anti-proliferative activity on mouse carcinoma [9 16] and breast cancer [10]. T. terrestris extracts also induce cell growth arrest and apoptosis by down-regulating NF-κB signaling in liver cancer cells, and exhibits weak cytotoxic effects to normal cells compared to cancer cells [11].…”
Section: Introductionmentioning
confidence: 99%
“…This extract of T. terrestris normalized the reduced level of glutathione enzyme for this induced toxicity. [24] The ethanolic extract from the T. terrestris was extracted from the aerial part and was examined for hepatoprotective activity against mercury induced hepatotoxicities in mice or rat. It was noted that on treating with mercury the levels of Aspartate transaminase (AST), Alanine transaminase (ALT), alkaline phosphatase (ALP), and Bilirubin were increased while that of Glutathione (GSH) content was decreased.…”
Section:  Hepatoprotective Activitymentioning
confidence: 99%